PELAKSANAAN STRATEGI PEMBELAJARAN PENDIDIKAN SENI BUDAYA SUB BIDANG STUDI SENI RUPA SMA NEGERI I KINALI PASAMAN BARAT - TUTI MAHYUDI, Ramalis Hakim, Erwin A (Serupa The Journal of Art Education, 2013)
The research are is aimed to describe (1) The Organizational Strategy, the implementation of arts and cultural education, specified in visual art learning strategy in Senior High School 1 Kinali, Pasaman Barat. (2) The Delivery strategy, the implementation of arts and cultural education, specified in visual art education learning strategy in Senior High School 1 Kinali, Pasaman Barat, (3) The Management Strategy, implementation of arts and cultural education, specified in visual art educations learning strategy in Senior High School 1 kinali, Pasaman Barat. The data of this research is taken from transcripts form or written form and oral form that come from informant resource who is interviewed by writer and based on the implementation learning strategy or from the phenomenon that have relationship with the focus of problem. The data is collected by observation method, interview and documentation study. The finding of the research will be a basic to plan or do arts and cultural instructional, specified in visual art instructional learning strategy appropriately. The finding of the research also can enrich the specific theoretic that will be referenced by the art teacher to choose and apply the learning strategies that appropriate with characteristic of the study that taught and for the students.